Synthesis of silicon dioxide hollow spheres - Gorbik, P.P.; Demchenko, Yu.O.; Dubrovin, I.V.; Kashin, G.N. (Functional Materials, 2009)
The hollow spherical particles of silicon dioxide have been synthesized by hydrolysis of dimethyl dichlorosilane (DMDCS) on the surface of spherical aerosol particles of DMDCS solution in nonpolar solvents. The formation conditions for spherical particles with prespecified structure and morphology have been determined. The phase and chemical composition as well as the morphology of the particles have been examined by X-ray diffraction, Auger electron spectroscopy, scanning electron microscopy, and atomic force microscopy.